2018
DOI: 10.1016/j.apsusc.2018.07.111
|View full text |Cite
|
Sign up to set email alerts
|

Reducing sheet resistance of self-assembled transparent graphene films by defect patching and doping with UV/ozone treatment

Abstract: Highlights Photochemical oxidation (UV/ozone treatment) of self-assembled solution-processed graphene films is demonstrated for the first time  The effect that photochemical oxidation has on self-assembled graphene films is a reduction of sheet resistance, the opposite of the earlier reported effect on CVD or mechanically exfoliated graphene  Edges as the dominant defect type in self-assembled graphene films play a crucial role in the presented defect density decrease  Photochemical oxidation is proposed a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…similar morphology to the material presented here, contains reactive edge defect sites that are responsible for sensitivity to various analytes [52]. After each purging step, and before subsequent exposure to CO2, the measured resistance returned to approximately the same baseline value, which indicates recovery of the sensing surface, without the need for any treatment, such as heating.…”
Section: Methodssupporting
confidence: 52%
See 1 more Smart Citation
“…similar morphology to the material presented here, contains reactive edge defect sites that are responsible for sensitivity to various analytes [52]. After each purging step, and before subsequent exposure to CO2, the measured resistance returned to approximately the same baseline value, which indicates recovery of the sensing surface, without the need for any treatment, such as heating.…”
Section: Methodssupporting
confidence: 52%
“…A negative TCR is commonly observed in single-layer graphene [10] and in multilayer graphene materials that possess a large number of defect sites, such as purposely introduced mechanical defects [49] or exfoliation-induced defects [50,51]. We previously demonstrated that liquid-phase exfoliated graphene, which is of similar morphology to the material presented here, contains reactive edge defect sites that are responsible for sensitivity to various analytes [52]. After each purging step, and before subsequent exposure to CO 2 , the measured resistance returned to approximately the same baseline value, which indicates recovery of the sensing surface, without the need for any treatment, such as heating.…”
Section: Methodsmentioning
confidence: 61%
“…The film area between contacts has dimensions of ~1500 µm x 190 µm. Taking into account film geometry yields sheet resistance of 3-7 kΩ sq -1 for our films, the smallest values reported for post-processing-free single-deposition Langmuir-Blodgett graphene films to date [16,18,20,22]. Such small sheet resistance is a result of fabrication process streamlining and careful four-terminal resistance measurements.…”
Section: Fabrication Of Graphene Films and Humidity Sensorsmentioning
confidence: 73%
“…The thin film is deposited on a pre-immersed substrate of choice following the Langmuir-Blodgett method [16,[18][19][20].…”
Section: Fabrication Of Graphene Films and Humidity Sensorsmentioning
confidence: 99%
See 1 more Smart Citation